PENAMPILAN PRAMUWISATA PADA ISTANA SIAK ASERAYAH AL–HASYIMIAH KABUPATEN SIAK - ,, Supiyan; Martina, Elti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the appearance of tour guides at the Asserayah Al-Hasyimiah Palace in Siak Regency and identify the challenges faced. The research employed a descriptive qualitative method using observation, interviews, and documentation. The results show that the tour guides’ appearance generally reflects Malay cultural values, but shortcomings remain, such as untidy hair and nails, inappropriate footwear, and habits like smoking or chewing gum while working. The main obstacle is the absence of written standard operating procedures regarding appearance. It is concluded that strengthening guidance, formulating appearance guidelines, and providing regular training are needed to improve tour guide professionalism and enhance the tourism image of Siak. Keywords: Appearance, Tour Guide, Asserayah Al-Hasyimiah Palace, Siak